Entry of the antipsychotic drug, olanzapine, into the developing rat brain in mono- and combination therapies [version 2; peer review: 2 approved] - Mark Habgood; Katarzyna Dziegielewska; Yifan Huang; Shuai Nie; Fiona Qiu; Norman Saunders (F1000Research, 2023)
Background: Olanzapine is used to treat schizophrenia and bipolar disorder in women of childbearing age. Continuation of psychotropic medications throughout pregnancy and lactation is often required as cessation could be dangerous for both mother and child. However, there is a lack of information on the transfer of these drugs into the developing brain. Methods: Sprague Dawley rats at three developmental ages: embryonic day E19, postnatal day P4 and non-pregnant adult females were administered unlabelled or radiolabelled (3H) olanzapine (0.15 mg/kg) either as monotherapy or in combination with each of seven other common medications. Similar injections were administered to pregnant E19 females to investigate placental transfer. Olanzapine in plasma, cerebrospinal fluid (CSF) and brain was measured by liquid scintillation counting after a single dose (acute) or following 5 days of treatment (prolonged). Results: Olanzapine entry into brain and CSF was not age-dependent. Prolonged olanzapine treatment reduced placental transfer from 53% to 46% (p<0.05). Co-administration of digoxin or lamotrigine with olanzapine increased its entry into the fetal brain, whereas paracetamol decreased its entry into the CSF. Placental transfer of olanzapine was increased by co-treatment with cimetidine and digoxin, whereas co-treatment with lamotrigine, paracetamol or valproate led to a substantial decrease. Repeated co-treatment of digoxin and olanzapine increased olanzapine transfer into the brain and CSF, but not across the placenta. Overall entry of olanzapine from maternally administered drugs into the fetal brain was higher after combination therapy with cimetidine and digoxin. Conclusions: Co-administration of olanzapine with some commonly used drugs affected its entry into the fetus and its developing brain to a greater extent than in adults. It appears that protection of the fetal brain for these drugs primarily comes from the placenta rather than from the fetal brain barriers. Results suggest that drug combinations should be used with caution particularly during pregnancy.